Adenylate Cyclase AcyA Regulates Development, Aflatoxin Biosynthesis and Fungal Virulence in Aspergillus flavus - Yang, Kunlong; Qin, Qiuping; Liu, Yinghang; Zhang, Limei; Liang, Linlin; Lan, Huahui; Chen, Chihao; You, Yunchao; Zhang, Feng; Wang, Shihua (Frontiers in Cellular and Infection Microbiology, 2016)
Aspergillus flavus is one of the most important opportunistic pathogens of crops and animals. The carcinogenic mycotoxin, aflatoxins produced by this pathogen cause a health problem to human and animals. Since cyclic AMP signaling controls a range of physiological processes, like fungal development and infection when responding to extracellular stimuli in fungal pathogens, in this study, we investigated the function of adenylate cyclase, a core component of cAMP signaling, in aflatoxins biosynthesis and virulence on plant seeds in A. flavus. A gene replacement strategy was used to generate the deletion mutant of acyA that encodes the adenylate cyclase. Severe defects in fungal growth, sporulation and sclerotia formation were observed in the acyA deletion mutant. The defect in radical growth could be partially rescued by exogenous cAMP analog. The acyA mutant was also significantly reduced in aflatoxins production and virulence. Similar to the former studies in other fungi, The acyA mutant showed enhancing tolerance to oxidative stress, but more sensitive to heat stress. Overall, the pleiotropic defects of the acyA deletion mutant indicates that the cAMP-PKA pathway is involved in fungal development, aflatoxins biosynthesis and plant seed invasion in A. flavus.